MENINGKATKAN HASIL BELAJAR IPS MELALUI MEDIA GAMBAR PADA SISWA KELAS IV SD NEGERI 3 MOLONA - Kasih, Waode Mitra (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2021)
This study aims to “Improving Social Studies Learning Outcomes through Image Media in Class IV Students of SD Negeri 3 Molona ​​South Buton Regency”. This research conducred in 2 cycles, each cycle includes: planning, implementation, observation, and reflection. The subjects of this study were the fourth grade students of SD Negeri 3 Molona for the 2020/2021 academic year, totaling 20 students consisting of 8 male students and 12 female students. Student learning outcomes on the pre-cycle test the percentage of completeness reached 30% with an average value of 57, in the implementation of the first cycle the percentage of completeness reached 50% with an average value of 63,5. Cycle II reached 80% with an average value of 75,5. This shows an increase in student learning outcomes from each cycle. The increase from pre-cycle to cycle I reached 25%, and the increase from cycle I to cycle II reached 25%. The increase from pre-cycle to cycle II reached 50%. So it can be concluded that through the use of image media it can improve sicial studies learning otcomes for fourth grade students of SD Negeri 3 Molona, South Buton Regency.